Authentic leadership and organizational commitment: The mediating role of positive psychological capital - Paulo Rego; Miguel Pereira Lopes; José Luís Nascimento (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: This study analyzes the mediating role of positive psychological capital in the relationship between authentic leadership and organizational commitment. Design/methodology/approach: This quantitative study presents a model in which were considered as variables mediating the relationship between authentic leadership and organizational commitment, the four dimensions of positive psychological capital (optimism, resilience, self-efficacy, hope). Findings: The results showed that positive psychological capital mediates the relationship between authentic leadership and organizational commitment. However, they also indicate that this mediation is only made for three of the four dimensions of positive psychological capital (self-efficacy, hope and optimism). They also show that resilience negatively affects organizational commitment. Originality/value: The value of this study is to strengthen the interest in the study of positive psychological capital as a mediating variable and the importance of development that each of its dimensions and the impact they may have on other variables, as demonstrated by the results.
Keywords: 650; authentic leadership; organizational commitment; positive psychological capital